2009
DOI: 10.1108/17506200910960851
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Greek Orthodoxy on entrepreneurship: a theoretical framework

Abstract: Purpose -The purpose of this paper is to offer a theoretical framework for the analysis of the eventual implications of Greek Orthodoxy for business and entrepreneurial activities in general. Design/methodology/approach -The paper examines the basic concepts, tenets and principles -in particular, those being of interest to business and entrepreneurship -of a specific religious worldview, Greek Orthodoxy. It then applies these religious norms to value-based entrepreneurial pursuits and assesses their potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 91 publications
0
14
0
1
Order By: Relevance
“…Since Weber's ([1922] 1978) seminal work on Protestant work ethics, the impact of religion and religious institutions on economic activity has had a long standing tradition in research. A more recent stream of empirical research has furthered our understanding of how the faith of an individual, such as Greek Orthodoxy (Gotsis & Kortezi 2009), Buddhism (Valliere 2008),…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Weber's ([1922] 1978) seminal work on Protestant work ethics, the impact of religion and religious institutions on economic activity has had a long standing tradition in research. A more recent stream of empirical research has furthered our understanding of how the faith of an individual, such as Greek Orthodoxy (Gotsis & Kortezi 2009), Buddhism (Valliere 2008),…”
Section: Discussionmentioning
confidence: 99%
“…Weber's (1930) seminal work on the Protestant Ethic and the Spirit of Capitalism laid the foundation to understand the mechanisms of how religion, an arguably personal attribute, can become prevalent in society and affect societal members. While Weber's (1930) thesis remains popular (Ryman & Turner 2007), more recent scholarship shows that the question of how religion broadly impacts the creation of new businesses remains topical (Audretsch et al 2013;Choi 2010;Dana 2009;Drakopoulou Dodd & Gotsis 2007;Drakopoulou Dodd & Seaman 1998;Galbraith & Galbraith 2007;Gotsis & Kortezi 2009;Essers & Benschop 2009;Neubert & Beard 2013;Valliere 2008). These studies can be viewed as part of a recent "theological turn" in the wider field of management and organizational studies, basically suggesting that religion 'supports' business (Dyck in press).…”
Section: Introductionmentioning
confidence: 99%
“…Honig (1998) found that married entrepreneurs who attend church regularly were more likely to succeed in business because of social capital and developed social networks. It was also found that family and religious ties in Greece enable and entrepreneurship over years (Gotsis and Kortezi, 2009). This was found in closed communities such as the Amish (Smith et al, 1997) and the Mennonites (Roessingh and Schoonderwoerd, 2005; Roessingh and Smits, 2010).…”
Section: Environmental and Cultural Influencesmentioning
confidence: 94%
“…Many (Anderson, Drakopoulou-Dodd, and Scott 2000;Carsrud and Brännback 2012;Smith 2009) suggest that there is value in studying entrepreneurship in different religious contexts because religion can influence the decision to become an entrepreneur. The religious environment affects innovation, creativity, and competitiveness (Gotsis and Kortezi 2009). However, no absolute effects are conferred on entrepreneurial activity by religion.…”
Section: Religionmentioning
confidence: 99%
“…According to Fattah and Butterfield (2006), this does not reflect an inconsistency as Muslims cannot be taken as a homogeneous group and neither can their religious views because a plurality of interpretations can be found as "Islam that unites Muslims divides them as well" (Fattah and Butterfield 2006). In Turkey, during the Ottoman Empire, Muslims were not allowed to undertake entrepreneurial activities, while non-Muslims were allowed to conduct business (Gotsis and Kortezi 2009). Only after the "exchange of populations" and establishment of the Turkish Republic did Muslims start to engage in entrepreneurial activities.…”
Section: Religionmentioning
confidence: 99%